Mowing: A cause of invasion, but also a potential solution for management of the invasive, alien plant species Erigeron annuus (L.) Pers. (1st October 2018) - Song, Uhram; Son, Deokjoo; Kang, Changku; Lee, Eun Ju; Lee, Kyoo; Park, Jeong Soo
Abstract: Erigeron annuus is one of the major invasive, alien plants in Korea, and therefore research to manage (control) this invasive plant is essential. In this research, studies were conducted to determine the mechanisms by which E. annuus became the dominant plant at a landfill site and to develop management strategies for this alien plant. Because the seeds and seedling stage did not have superior adaptations to disturbed soil, demonstrate allelopathy, outcompete other species, or show rapid growth, the disturbance from mowing was likely the primary reason for the dominance of E. annuus . The areas without mowing showed a significant decrease in the coverage of E. annuus, whereas the mowed (managed) areas showed a significant increase. Additionally, mowing once increased the weight of reproductive organs by 50% and suppressed the growth of native species. Thus, the primary factor in the invasion of the alien species E. annuus was mowing, and, to control such an invasion, areas should be protected from mowing. Additionally, with selective mowing that targeted only E. annuus, mowing three times produced only approximately 10% of the reproductive organ biomass compared with that of the control. Because the flower stalk of E. annuus was relatively tall compared with that of native species in early summer, selective mowing might also provide a solution to control invasions of E. annuus . Therefore, with improved ecological understanding of the site and species, mowing of the right target during the optimal season and at an appropriate frequency is an environmental friendly solution to the management of E. annuus . Highlights: We examined responsible factor for the Erigeron annuus invasion in managed reclaimed areas. Mowing was a responsible factor for Erigeron annuus invasion. Changing mowing season and mowing frequency suppressed invasion. Appropriate mowing could be a potential solution for controlling Erigeron annuus invasion.